Effect of acidity consumption/production on the pH of aeration tank during the biodegradation of acetic acid/epichlorohydrin - Yoon, SH; Kim, HS; Chung, YC (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
In order to elucidate the biologically driven pH fluctuation phenomena in industrial wastewater treatment, the contrary effects of acetic acid (AA) and epichlorohydrin (ECH) on the pH of aeration tank were investigated. Two simple equations were derived to estimate optimum neutralization pHs for the biological AA/ECH wastewater treatment, and the calculated optimum neutralization pHs were compared with experimental results. The pH in aeration tank was expected to fluctuate sharply with the smallest deviation of neutralization pH from the optimum value, However experimental results showed that real pH fluctuation is smaller than the theoretical one. It was considered that carbonate buffer in aqueous system relieves the pH fluctuation. The deviation between experimental and theoretical optimum neutralization pH could be mainly caused by volatility of AA and ECH. The deviation was larger with ECH wastewater of which volatility is larger than AA. Finally, this theory was successfully applied to the real petrochemical wastewater treatment. The pH of aeration tank was properly maintained when acidified wastewater (pH 3.4) was supplied.) (C) 2002 Elsevier Science Ltd. All rights reserved.